“Implementación de un dispositivo electrónico para la identificación, cuantificación de carbonos en el cultivo de lechuga en la carrera de Agronomía de la Universidad Técnica de Cotopaxi” - Masapanta Quishpe, Joselyne Estefania (2023)
The technological proposal consists of the implementation of an electronic device for the identification and quantification of carbon dioxide (CO2) and methane (CH4) in open environments, in order to verify the growth of lettuce plants and the production is faster. Go controlling edaphoclimatic variables to reduce costs and have a better production gain; Field analyzes were carried out on the terraces of the Technical University of Cotopaxi in the Salache extension in the Agronomy Career.